The Infected Eye Clinical Practice and Pathological Principles - Laver, Nora V.; Specht, Charles S. (Springer International Publishing : Imprint: Springer, 2016)
This book addresses the diagnosis and treatment of common ocular infections. Relevant pathological principles are described to provide a basis for the understanding of these disorders. The epidemiology of infection as a class of ocular disease and the pathological effects of infectious processes in tissue are discussed in introductory chapters. These fundamentals are explained and reinforced with tables and selected illustrations of tissue pathology. Further chapters by leading clinical specialists describe recommended approaches to infections of the eye and periocular tissues as these conditions occur in adults and children. Illustrative tables and algorithms enhance the discussion, making key principles accessible to the busy clinician. The final chapters provide a guide to relevant microbiological techniques, recommendations for specimen collection and transport, and a survey of antimicrobial therapy for the care of patients with ocular infectious diseases.